(3GdJYQa dePgH GdJUhas - (3GdcdGHGPj , eMeO Hf EHQGgje Hf jYbhH, CHh HcQ,J (B380 (3g` s
(3ChdgG (B:s
(3hSejJg HcJGH GdJYQja dePgH Cgd GdJUha HGH de JSejI GdUhajI UhajI s
(3BNQgG (B:s
(3bGd CHh YHO Gddg GdfHGLi GdSeGY EeG EKGQI acQI Ch cSH YHQI JeJ cJGHI cJGH GdJYQja HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B295 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B212s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B419s
Keywords: (3GdJUha hGdBOGH GdTQYjIs